Mathematics Make Students Confused and Anxious: a Comparisons Between Australia, Indonesia, and Singapore in The 2015 Timss - Safari, NFN (Indonesian Journal of Educational Assessment, 2020)
The main purpose of this study is to find out  the perceptions about Mathematics that confuse and anxious 2015 TIMSS participants in Australia, Indonesia, and Singapre. The data in this study is the 2015 TIMSS data that has been released to the public and has available  for development purpose research. The research method used is quantitative method. The population of this study is students' perceptions of Mathematics subject that confuse and worry students aged 15 years in three countries who are studying in 2015, while the sample is 15-year-old students’ perceptions  in these countries. The data in this study were in the form of questionnaires which were answered by 16599 students from these three countries. Based on the results of the analysis of variance, there is a significant difference (P <0,000) on students' perceptions about mathematics subject that confuse and worry students in these three countries (Sig. 0,000). The reliability of students' abilities is the same, Australia = 0.74, Indonesia = 0.75; and Singpura = 0.75. The conclusion is most students in these three countries stated "disagree a lot" about mathematics make students confuse and worry.